2018
DOI: 10.1039/c8qo00232k
|View full text |Cite
|
Sign up to set email alerts
|

Directing group assisted ZnI2-catalyzed cyclopropanation of indoles via 2-furylcarbenoids

Abstract: An efficient method for the synthesis of cyclopropane-fused indolines via a Zn2I catalyzed cyclopropanation of indoles and enynones was reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…The Xu group reported a directing group assisted ZnI 2 ‐catalyzed cyclopropanation of indoles with ene‐yne‐ketones via 2‐furylcarbenoids (Scheme ) . They found that both pyrimidine and N , N ‐dimethylcarbamoyl at N 1 position of indoles could realize this cyclopropanation to deliver products efficiently.…”
Section: Other Reactions Of Indole‐n‐carboxamidesmentioning
confidence: 99%
See 1 more Smart Citation
“…The Xu group reported a directing group assisted ZnI 2 ‐catalyzed cyclopropanation of indoles with ene‐yne‐ketones via 2‐furylcarbenoids (Scheme ) . They found that both pyrimidine and N , N ‐dimethylcarbamoyl at N 1 position of indoles could realize this cyclopropanation to deliver products efficiently.…”
Section: Other Reactions Of Indole‐n‐carboxamidesmentioning
confidence: 99%
“…The Xu group reported a directing group assisted ZnI 2catalyzed cyclopropanation of indoles with ene-yne-ketones via 2-furylcarbenoids (Scheme 34). [43] They found that both pyrimidine and N,N-dimethylcarbamoyl at N1 position of indoles could realize this cyclopropanation to deliver products efficiently. When indole-N-carboxamides 134 and ene-yne-ketones 135 were treated with 10 mol % ZnI 2 at 30°C in 1,2-dichloroethane, indole derived cyclopropane products 136 could be obtained in excellent yields and high regioselectivity.…”
Section: Other Reactions Of Indole-n-carboxamidesmentioning
confidence: 99%
“…Lopez et al [47] reported the catalytic generation of zinc(II) furylcarbenes derived from carbonyl ene-yne compounds and zinc salts, as well as their reactivity in addition and insertion processes with styrene (Scheme 1(b)). Recently, while collating the data for the present article, Xu et al [49] explored the access to similar products via ZnI2-catalyzed cyclopropanation of indole with enynone. Notwithstanding the success, the investigation is limited to low functional group tolerance; certain N-substituent of indole failed to generate the desired product (Scheme 1(c)).…”
Section: Introductionmentioning
confidence: 99%
“…3 Typically, strategies for the construction of indolines containing a cyclopropane moiety strongly rely on transition-metal-catalyzed [2+1] cycloadditions of indoles with diazo compounds 1e,4 or tosylhydrazones. 5 Cyclopropanation of indoles with metal carbenes to construct these structural units have been reported recently by Zhou, 6 Pirovano, 7 and other groups 4,5,8 (Scheme 1). Noteworthy is that transition-metal catalysts were essential in the above strategies, while metal-free approaches were reported only rarely; this makes the available protocols relatively unattractive from a sustainable perspective.…”
mentioning
confidence: 97%